Fatty acid composition of Achillea arabica Kotschy and Achillea teretifolia Willd. from three different locations - Kolaç, Turgay; İzci, Yunus; Paşahan, Aziz (İzzet KARA, 2026)
The genus Achillea (Asteraceae) comprises numerous species with significant medicinal and industrial applications, largely attributed to their diverse phytochemical profiles, including fatty acids. This study investigated the fatty acid composition of Achillea arabica Kotschy and Achillea teretifolia Willd. collected from three distinct locations in Malatya Province, Türkiye. Plant materials were extracted with n-hexane using a Soxhlet apparatus, and fatty acid methyl esters (FAMEs) were analyzed by gas chromatography with flame ionization detection (GC-FID). A total of 32 fatty acids were identified, with statistically significant (p < 0.001) variations observed in their composition between species and collection sites. In A. arabica, lauric acid (25.0–32.2%) and palmitoleic acid (21.2–23.6%) were significantly more abundant than in A. teretifolia (p < 0.001). In A. teretifolia, capric acid (8.3–9.2%), arachidic acid (6.4–7.7%), and caproic acid (8.0–9.3%) were found at significantly higher levels than in A. arabica (p < 0.01). Statistical analysis (Student's t-test) revealed significant differences (p < 0.05) between species for the following major fatty acids: lauric acid, palmitoleic acid, capric acid, arachidic acid, and tricosanoic acid. These findings highlight geographical influences on fatty acid profiles and underscore the potential of these species as sources of bioactive lipids for pharmaceutical and nutraceutical applications.
Keywords: Achillea arabica; Achillea teretifolia; Fatty acids; Malatya; Chemotaxonomy